1976
DOI: 10.1111/j.1476-5381.1976.tb07638.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Responses to Adrenal Field Stimulation as a Measure of Adrenal Catecholamine Release

Abstract: A new method for studying adrenal medullary release is described in pithed rats using field stimulation of an entire adrenal gland. The increases in blood pressure in response to field stimulation of the gland consisted of an initial short, variable component, due to stimulation of adrenergic vasomotor neurones and a secondary, longer lasting component, due to medullary catecholamine release. Removal of the initial component by drugs or cardiac/coeliac ganglionectomy did not affect the magnitude of the seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
1982
1982

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It is well established that the adrenal medulla remains functional after chemical sympathectomy with 6-OHDA (Clarke & Romanyshyn, 1976) and, morevoer, several biochemical studies have shown increased activity of the adrenal medulla in sympathectomized animals. (Mueller, Thoenen & Axelrod, 1969;Mueller, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the adrenal medulla remains functional after chemical sympathectomy with 6-OHDA (Clarke & Romanyshyn, 1976) and, morevoer, several biochemical studies have shown increased activity of the adrenal medulla in sympathectomized animals. (Mueller, Thoenen & Axelrod, 1969;Mueller, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, similar experiments were performed in a group of 6-hydroxydopamine (6-OHDA)-treated animals in order to determine whether adrenal medullary NE release could be modulated by the carotid sinus and cardiopulmonary reflexes. 6-Hydroxydopamine has been shown to destroy adrenergic nerve terminals effectively without destroying adrenal medullary catecholamine-containing cells or other nerves (Thoren and Tranzer, 1968;Prentice and Wood, 1975;Clark and Romanyshyn, 1976).…”
Section: Treatment With 6-hydroxydopaminementioning
confidence: 99%